Peningkatan Hasil Belajar Materi Q.S At- Tiin Melalui Metode Make a Match Dikelas IV SD Negeri 16 Timbulun - Qadri, Filailatil (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to analyze the comparison between the Student Centered Learning (SCL) method and conventional methods in improving the learning outcomes of Islamic Religious Education (PAI) students at SD Negeri 16 Timbulun. Using a quantitative approach, the study collected data through pre-test and post-test as well as observations during the learning process. The results indicate that the SCL method is more effective in enhancing students’ understanding of Surat Al-A’la compared to conventional methods. Students taught using the SCL method showed significant improvements in active engagement, concept understanding, and reflective abilities. Therefore, it can be concluded that SCL is a better method to be applied in PAI learning at the elementary school level.